2017
DOI: 10.1002/aoc.3926
|View full text |Cite
|
Sign up to set email alerts
|

Biohybrid based on layered terbium hydroxide and applications as drug carrier and biological fluorescence probe

Abstract: Aspirin (abbr. ASA) is intercalated into the layered terbium hydroxide (LTbH) by anion exchange method. Structure, chemical compositions, thermostability, morphology, luminescence property, cytotoxic effects and controlled-release behaviors have been investigated. The ASA molecules may embed between layers with monolayered vertical arrangement, and the thermal stability of organics was enhanced after intercalation. The Tb 3+ luminescence in ASA-LTbH composites was enhanced compared with LTbH precusor and the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…62 Further work by this group developed LEuH intercalated with naproxen (nap), and LTbH intercalated with aspirin, diclofenac, and indomethacin (asa, dic, and imc). [63][64][65] It was demonstrated that LEuH-nap and the LTbH-drug intercalates have high biocompatibility (>80%) in multiple human cancer cell lines at concentrations up to 100 µg ml −1 . The majority of drug was released from LEuH-nap and LTbH-asa in the first 3 hours, 63,64 whereas LTbH-dic and LTbH-imc showed sustained release over 25 h. 65 It was found also that LEuH and LTbH showed vastly increased luminescence intensities after intercalation with nap and asa respectively, owing to efficient energy transfer between the host and guest species.…”
Section: Introductionmentioning
confidence: 99%
“…62 Further work by this group developed LEuH intercalated with naproxen (nap), and LTbH intercalated with aspirin, diclofenac, and indomethacin (asa, dic, and imc). [63][64][65] It was demonstrated that LEuH-nap and the LTbH-drug intercalates have high biocompatibility (>80%) in multiple human cancer cell lines at concentrations up to 100 µg ml −1 . The majority of drug was released from LEuH-nap and LTbH-asa in the first 3 hours, 63,64 whereas LTbH-dic and LTbH-imc showed sustained release over 25 h. 65 It was found also that LEuH and LTbH showed vastly increased luminescence intensities after intercalation with nap and asa respectively, owing to efficient energy transfer between the host and guest species.…”
Section: Introductionmentioning
confidence: 99%
“…57 More recently, Gu and co-workers generated a naproxen-intercalated layered europium hydroxide, which was found to release the incorporated drug over about 200 min, retain the inherent luminescence of Eu 3+ , and to be highly biocompatible. 58 Finally, Ju and Gu have reported an aspirin intercalate of a layered terbium hydroxide formed by ion exchange, and observed enhanced Tb luminescence intensity and sustained drug release over 10 h. 59 Therefore, it appears that LRH-drug composites have great promise, but more work is required to explore this in detail.…”
Section: Introductionmentioning
confidence: 99%
“…[61][62][63] These ion-exchangeable and exfoliatable substances have a great deal of exibility in terms of their chemical composition 61,[64][65][66] and are now regarded as a basis for promising bioactive theranostic materials. 67,68 From the ndings of the current study, a paper-like material couldn't be classied as a layered rare earth hydroxide as the positions of the maxima in its diffraction pattern (see Fig. 2) are incompatible with the LRHs' structure.…”
Section: Resultsmentioning
confidence: 73%